Multiepitope Dendrimeric Antigen-Silica Particle Composites as Nano-Based Platforms for Specific Recognition of IgEs - Gil-Ocaña, Violeta; Jimenez, Isabel M.; Mayorga, Cristobalina; Doña, Inmaculada; Céspedes, Jose Antonio; Montañez, Maria I.; Vida, Yolanda; Torres, Maria J.; Perez-Inestrosa, Ezequiel (Frontiers in Immunology, 2021)
β-lactam antibiotics (BLs) are the drugs most frequently involved in drug hypersensitivity reactions. However, current in vitro diagnostic tests have limited sensitivity, partly due to a poor understanding of in vivo drug–protein conjugates that both induce the reactions and are immunologically recognized. Dendrimeric Antigen-Silica particle composites (DeAn@SiO2), consisting on nanoparticles decorated with BL-DeAns are promising candidates for improving the in vitro clinical diagnostic practice. In this nano-inspired system biology, the synthetic dendrimer plays the role of the natural carrier protein, emulating its haptenation by drugs and amplifying the multivalence. Herein, we present the design and synthesis of new multivalent mono- and bi-epitope DeAn@SiO2, using amoxicillin and/or benzylpenicillin allergenic determinants as ligands. The homogeneous composition of nanoparticles provides high reproducibility and quality, which is critical for in vitro applications. The suitable functionalization of nanoparticles allows the anchoring of DeAn, minimizing the nonspecific interactions and facilitating the effective exposure to specific IgE; while the larger interaction area increments the likelihood of capturing specific IgE. This achievement is particularly important for improving sensitivity of current immunoassays since IgE levels in BL allergic patients are very low. Our data suggest that these new nano-based platforms provide a suitable tool for testing IgE recognition to more than one BL simultaneously. Immunochemical studies evidence that mono and bi-epitope DeAn@SiO2 composites could potentially allow the diagnosis of patients allergic to any of these drugs with a single test. These organic–inorganic hybrid materials represent the basis for the development of a single screening for BL-allergies.